STUDIES ON MICROBIOLOGICAL QUALITY OF SPROUTS OF MUNG BEAN (VIGNA RADIATE L.) - Chauhan, Shilpi; Saini, Ankit; Singh, Devendra Pratap; Dhaked, Umesh; Gupta, Poonam (Journal of Drug Delivery and Therapeutics, 2013)
Sprouts are now well known for their high nutritive value and digestibility. They are rich in enzymes, bioavailable vitamins, minerals, amino acids and fibers. Sprouts are low in fat and calories, being rich in nutrients and known to promote health, sprouts now a days are available in most of the grocery stalls. Survey of sprouted seeds available at retail venders has shown the presence of pathogenic bacteria like E. coli 0157, Salmonella and Listeria monocytogens, which is of concern for health conscious public. In the present study an attempt has been made to identify and examine the microorganisms present in seed sprouts of mung bean. Key Words: Mung Bean Sprouts, Morphological Identification, Biochemical Characteristics.